Novel cassette chromosome recombinases CcrA8B9 catalyse the excision and integration of the staphylococcal cassette chromosome mec element. (8th December 2022) - Xiao, Jinhe; Huang, Jianguo; Xue, Xuemei; Wang, Chen; Sun, Yanting; Zheng, Liangjun; Zhao, Xu; Wang, Xiaokun; Zhao, Xin; Xue, Huping
Abstract: Objectives: A defining feature of MRSA is the SCC mec element. The excision and integration of SCC mec elements are catalysed by Ccr recombinases. Currently, seven ccrA, eight ccrB and two ccrC allotypes have been described. However, there have been no recent reports of a novel Ccr recombinase and thus this area should be explored. Methods: According to the proposed criteria of the International Working Group on the Classification of Staphylococcal Cassette Chromosome Elements (IWG-SCC) committee, novel ccr genes were explored by searching the genome of our laboratory staphylococcal strains, which were isolated from bovine mastitis in Northwest China. The biological activity of the novel Ccr recombinases to excise and integrate SCC mec elements was determined. The distribution of the novel ccr genes in staphylococci was conducted by querying the NCBI nr/nt database. Results: We report a set of novel Ccr recombinases CcrA8B9, which share nucleotide identities of 46.6%–50.2% and 47.4%–52.8% with the ccrA and ccrB alleles, respectively. We used PCR to show that CcrA8B9 can excise and integrate the SCC mec element. Furthermore, using NCBI BLAST we showed that the ccrA8B9 genes exist in other staphylococcal strains. Unlike the common ccr genes, ccrA8B9 is located outside the SCC mec /SCC element. Conclusions: The novel Ccr recombinases CcrA8B9 can help excise and integrate SCC mec /SCC from the genome and provide a new way to facilitate the transmission of SCC mec /SCC elements among staphylococci.